The role of suffixation to build neologisms in modern English - Erkinova, Lola Dilshod qizi (The Lingua Spectrum, 2026)
This research indicates various ways of making neologisms and implementing them in the usage of language in proper places. One of the basic ways of building neologisms considered suffixation. Through different suffixes, new meaning can be confirmed into language usage. There are two sections to the paper. Taking into account earlier research on the issue, we attempted to define the term "neologism" in the first section of the paper. As a result, a neologism is a relatively new word that has not yet been incorporated into the mainstream language, but it may be on its way to becoming so. This research indicates various suffixation to make new senses in the linguistics. One of the most active and effective methods for producing neologisms in contemporary English is suffixation, especially in social media, technical professions, and informal communication. English speakers can systematically create new nouns, verbs, and adjectives that represent changing cultural, technological, and social realities by appending bound morphemes to the end of preexisting words (bases).